A Modular Approach to Inorganic Phosphazane Macrocycles. Issue 31 (21st April 2017) - Plajer, Alex J.; García‐Rodríguez, Raúl; Benson, Callum G. M.; Matthews, Peter D.; Bond, Andrew D.; Singh, Sanjay; Gade, Lutz H.; Wright, Dominic S.
Abstract: Inorganic macrocycles, based on non‐carbon backbones, present exciting synthetic challenges in the systematic assembly of inorganic molecules, as well as new avenues in host–guest and supramolecular chemistry. Here we demonstrate a new high‐yielding modular approach to a broad range of trimeric and hexameric S‐ and Se‐bridged inorganic macrocycles based on cyclophosphazane frameworks, using the building blocks [S=(H)P(μ‐NR)]2 . The method involves the in situ generation of the key intermediate [E . . . . . _ (S . . . . . _ )P(μ‐NR)]2 2− (E=S, Se) dianion, which can be reacted with electrophilic [ClP(μ‐NR)]2 to give P III /P V hexameric rings or reacted with I2 to give trimeric P V variants. Important issues which are highlighted in this work are the competitive bridging ability of S versus Se in these systems and the synthesis of the first air‐stable and chiral inorganic macrocycles. Abstract : Give me a ring : A range of new S‐ or Se‐bridged phosphazane macrocycles can be obtained using the dimeric dianions [S=(Se)P(μ‐N t Bu)]2 2−, either through reactions with the dichlorophosphazane dimers [ClP(μ‐NR)]2 or by oxidation with I2 . This approach allows variation of the organic substituents in this class of inorganic macromolecule for the first time, and the introduction of chirality.